PEMBERDAYAAN PETANI BAWANG MELALUI EDUKASI HAK KEKAYAAN INTELEKTUAL DAN PENGEMBANGAN OLAHAN AGRIBISNIS - Nando Dwi Kurniawan; Triyan Bayu Pratama; Agung Abdul Rahman Wiyono (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Empowering onion farmers is essential to increase product added value and strengthen the competitiveness of local agribusiness. Farmers commonly face challenges such as limited understanding of Intellectual Property Rights (IPR), lack of innovation in processed products, and suboptimal marketing strategies. This community service program aims to enhance farmers’ capacity through IPR education and the development of locally based agribusiness products. A participatory method was applied, including counseling, training, assistance in processing onion-based products, and socialization on trademark protection and product packaging. The results show improved farmer awareness of IPR, particularly trademark registration, along with enhanced skills in producing value-added products such as packaged fried onions, chili onion sauce, and other derivatives. Additionally, farmers have begun to understand that effective marketing strategies and product branding can increase economic value, independence, and sustainable competitiveness.